GA Document 157 : International 2021 - Futagawa, Yoshio; Saito, Hitomi; Nakamura, Akiyo; Sekimoto, Reiko (Tokyo : A.D.A. EDITA Tokyo Co., Ltd., 2021)
Wine Cellar in Alentejo Coast / Aires Mateus ; Kröller-Müller Museum / Tadao Ando ; Artist Atelier - London Design District / Barozzi Veiga ; MACBA Extension / Christ & Gantenbein + Harquitectes ; Sports and Concert Complex-St. Petersburg / COOP HIMMELB(L)AU ; Zhangjigang Art Museum / Atelier Deshaus ; EDP Headquarters / ELEMENTAL ; ART ROCK, Desert Rock for AIUIa / Ensamble Studio ; Le Dome Winery / Foster + Partners ; Qianhai New City Center Landmark / Sou Fujimoto ; China Medical University Museum of Medical Science and Art / Frank O. Gehry ; Toranomon-Azabudai / Thomas Heatherwick ; iCarbonX Headquarters / Steven Holl ; Kokage-gumo / Junya Ishigami ; Guoshen Museum / JKMM Architects ; Super Resin, Inc. Sakahama / Johnston Marklee ; Shifting Tower / Christian Kerez ; ENGAWA-Calouste Gulbenkian Foundation Southern Apex / Kengo Kuma ; Jiaxing Train Station / MAD Architects ; Vialia Estación de Vigo / Morphosis ; Expo Pavilion 2.0 / MVRDV ; Office in Mishima / Ryue Nishizawa ; Aviation Academy / Jean Nouvel ; Academic Hub and Library, Technological University Dublin / O'Donnell + Tuomey ; Toranomom Hills Station Tower / OMA ; Academic Wood Tower / Patkau Architects + MacLennan Jaunkalns Miller Architects ; New Toronto Courthouse / Renzo Piano Building Workshop ; Ummara / Michel Rojkind + AmasA Estudio ; Villa Virreyes / Fernando Romero ; Puyuan Design and Event Center / Kazuyo Sejima ; Orchard Hotel / selgascano ; BYHMC-Babyn Yar Holocaust Memorial Center / Wolgang Tschapeller ; Van B / UNStudio ; Taoyuan Museum of Art / Riken Yamamoto ; Thermal Spa / ZAO/standardarchiotecture ; Majiayao Ruins Observatory / Zhu Pei
boek